CAUSES AND TREATMENT OF INFERTILITY (World Bulletin of Public Health, 2023)
This article discusses the problems, statistics of the causes of infertility in men and women and their modern solutions. Contrary to popular belief, infertility affects both women and men equally. That is, the quantitative ratio of infertile patients of each sex is approximately the same. For this purpose, modern fertility clinics have been created, which practice well-proven methods of treating infertility.